2005
DOI: 10.1161/01.cir.0000162477.70955.5f
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hemoglobin Levels With Clinical Outcomes in Acute Coronary Syndromes

Abstract: Background— In the setting of an acute coronary syndrome (ACS), anemia has the potential to worsen myocardial ischemia; however, data relating anemia to clinical outcomes in ACS remain limited. Methods and Results— We examined the association between baseline hemoglobin values and major adverse cardiovascular events through 30 days in 39 922 patients enrolled in clinical trials of ACS. After adjustment for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
312
5
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 607 publications
(380 citation statements)
references
References 57 publications
20
312
5
20
Order By: Relevance
“…This association remains significant after adjustment for other risk markers that could be related to anemia, such as age and renal impairment [3,12,13,14,15,16,17,18]. However, statistical significance in multivariate analysis is not a sufficient condition for a clinically relevant improvement in prognostic assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association remains significant after adjustment for other risk markers that could be related to anemia, such as age and renal impairment [3,12,13,14,15,16,17,18]. However, statistical significance in multivariate analysis is not a sufficient condition for a clinically relevant improvement in prognostic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Low hemoglobin has been established as an independent predictor of recurrent events [3]; however, it is not included in risk scores for ACS. Considering that hemoglobin values are widely available at admission, it is useful to evaluate whether this information should be considered within risk scores.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital‐based studies have reported prevalence up to ≈30% 1, 2. Although anemia has been independently associated with increased mortality in a variety of conditions including chronic kidney disease,3 heart failure,4 and acute coronary syndromes,5 observational studies investigating the association between anemia and mortality in stroke have shown conflicting results. Early studies found no association between anemia and stroke outcomes6, 7; however, others have found both low and high hemoglobin levels to be associated with increased mortality,8, 9, 10 suggesting a U‐shaped relationship.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] On the other hand, cardiorenal anemia syndrome, in which the simultaneous presence of CKD, anemia, and heart failure creates pathological reciprocal connections, thereby resulting in an adverse synergistic impact on morbidity and mortality, is now attracting more attention. 7,8) However, few data are available concerning the impact of CKD and anemia on clinical outcomes among AMI patients undergoing primary percutaneous coronary intervention (PCI) in Japan, 9,10) and in terms of CKD concomitant with anemia, only the recent report from Matsue and colleagues has examined the longterm prognostic impact of CKD/anemia combination after hospital discharge in Japanese AMI patients.…”
mentioning
confidence: 99%